10. NEW PARADIGMS FOR DISCOVERY. (9th April 2019) - Carpenter, William
Abstract: Schizophrenia conceptualized as a specific disorder has resulted in substantial knowledge but has not been validated as a disease entity. An alternative concept of schizophrenia as a heterogeneous clinical syndrome requiring deconstruction. Syndrome status and implications was proposed over 40 years ago and is formally stated in DSM-5. The modest progress in understanding pathophysiological mechanisms and limited progress in therapeutics has resulted in the development of new paradigms for discovery. Four paradigms sensitive to heterogeneity and to across diagnostic boundaries are currently engaged in opening new views and scientific approaches to understanding psychopathology and will be represented in the panel presentations. Each has the potential to increase knowledge on psychopathology and guide future modifications in nosology and diagnostic concepts [think DSM-5.1, DSM-5-2, etc.] 1. Roman Kotov will present on reconceptualization of schizophrenia from the HiTOP perspective including continuity with normal functioning, heterogeneity within the disorder, and its relations to mania, schizotypy, and other conditions. This new paradigm has immediate implications for research and clinical care. New data will be presented from an epidemiologic study of psychosis. 2. Aristotle Voineskos will illustrate the RDoC paradigm with the study of social cognition as a single dimension including deficit schizophrenia, non-deficit schizophrenia and non-ill participants. Several emerging findings from an ongoing RDoC initiative show that a dimensional approach coupled with multivariate analytics, can be successfully used to identify brain-behavior subtypes related to social impairment cutting across a full spectrum of individuals from non-ill participants through to people with schizophrenia who are most impaired. 3. Brett Clementz will illustrate the B-SNIP paradigm showing that deviation in level of intrinsic neural activity (present in ongoing signals recorded from humans with EEG/MEG) is observed in psychosis. Translational models of intrinsic activity deviations hold promise for identifying multiple distinct physiological mechanisms for psychosis manifestation. B-SNIP data show that psychosis Biotypes, but not DSM diagnoses, differ on level of intrinsic activity, and that clozapine treatment enhances this signal, bringing Biotype-1 cases closer to normal and taking Biotype-2 cases farther from normal. Such results yield information about how to predict psychosis cases that can benefit from this specific treatment. 4. Alan Anticevic will present a multivariate linear and nonlinear framework for mapping of neuro-behavioral relationships in dimensional geometric embedding (N-BRIDGE), which will be linked to effects of neuropharmacology, biophysical computational models and transcriptomic effects in humans. Each presentation will include new data. Sarah Morris will discuss these paradigms including their role in research funding and regulatory issues.